PIM1 induces hypoxia-related fibroblast senescence in a mouse model of stress urinary incontinence - Ya Xiao; Mao Chen; Lingyun Li; Liying Chen; Xiaoyu Tian; Xiaoyu Huang; Fangyi Zhu; Bingshu Li; Li Hong (PLoS ONE, 2025)
Objective This study aims to explore the contribution of PIM1 kinase-mediated cellular senescence to the pathogenesis of stress urinary incontinence (SUI) and to assess the therapeutic potential of inhibiting PIM1. Methods A mouse model of SUI was developed through vaginal balloon dilation to investigate hypoxia in the vaginal wall, utilizing HypoxyprobeTM-1 staining and HIF-1α expression analysis. Cellular senescence was evaluated by measuring SA-β-gal activity, senescence-associated heterochromatin foci (SAHF) formation, Ki67 expression, and γH2A.X accumulation. In vitro experiments involved the use of hypoxia-treated fibroblasts subjected to PIM1 knockdown or treatment with AZD-1208. Functional outcomes were assessed through bladder leak point pressure tests and histological analysis. Results The study revealed that the SUI model exhibited significant reductions in vaginal wall blood flow and an increase in hypoxia markers. Indicators of cellular senescence were significantly elevated in SUI tissues, alongside a notable upregulation of PIM1. Mechanistically, PIM1 facilitated senescence through two pathways: inducing cell cycle arrest via activation of P16/P21 and impairing DNA repair through the formation of SAHF. Hypoxic conditions significantly enhanced PIM1 expression and senescence markers in fibroblasts, effects that were effectively reversed by PIM1 inhibition. Treatment with AZD-1208 led to significant improvements in bladder function and a reduction in senescence burden in vivo. Conclusion This study identifies PIM1 as a critical mediator linking hypoxia-induced cellular senescence to the development of SUI. The PIM1 inhibitor AZD-1208 demonstrates promising therapeutic effects, offering a novel approach for the treatment of SUI, with particular relevance for postpartum prevention. These findings elucidate a comprehensive hypoxia-PIM1-senescence pathogenic pathway and identify a potential target for clinical intervention.